Using digital art to explore creativity in visually gifted elementary students - Dela Peña, Maria Cecilia O. (2008)
The value of the study was to evaluate important features in the creative thinking of the visually gifted child, and to evaluate their potential through an educational computer activity that can be accomplished in a day. The study employed a pretest-posttest method. From the 13 nominated visually gifted Grade 6 students, there was no confirmed visually gifted child based on both the Torrance Test of Creative Thinking Figural Form B and the Modified Rubrics. This brief look at a representative finding suggests the richness and complexity of a child's expressive products. Any single measure of creativity is rarely sufficient by itself. Documentation of past activities and achievement is called for as the most valid method of predicting the future creativity for older children.